First Stereoselective Total Synthesis of Anti-Inflammatory Metabolite Penicillinolide A - Reddy, Mopuri Sudhakar; Manikanta, Gembali; Krishna, Palakodety Radha (Synthesis, 2019)
The first asymmetric total synthesis of penicillinolide A is described. Key steps of the synthesis involve Jacobsen’s hydrolytic kinetic resolution (HKR), chelation controlled allylation, Brown’s asymmetric allylation, hydroboration, and Yamaguchi lactonization.
Keywords: Jacobsen’s hydrolytic kinetic resolution (HKR); chelation controlled allylation; Brown’s asymmetric allylation; hydroboration; Yamaguchi lactonization